The Effect of Real Exchange Rate Undervaluation on Economic Growth - Seraj, Mehdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Over the years, economists have come to agree that a poorly handled exchange rate would do more harm than good to the growth efforts of any economy. However, the exact relationship between the exchange rates and the economic growth is not well understood. This study uses Rodrik (2008) paper on “the real exchange rate and economic growth” as a benchmark work to carry out a comprehensive analysis of the impact of currency undervaluation on economic growth. To this end this thesis is organized into four independent studies. The first two are panel data studies where the economic growth is regressed on real exchange rate undervaluation. The two studies differ from each other mainly in two ways. One difference is the way that currency undervaluation is measured, and the second difference is the way the growth equation is modelled. In short, second study-which is referred as fundamental equilibrium exchange rate model- is intended to be an improvement on the first study –which is referred as the Balassa-Samuelson effect based Rodrik approach. The third research examines how the real exchange rate undervaluation impacts economic growth by using time series analysis. The relationship studies for four countries, -namely Germany, South Africa, Mexico, and Cameroon- with different exchange rate regimes. The studies check if the relationships are symmetric or asymmetric; and accordingly uses ARDL or NARDL methodologies to investigate how the real exchange rate undervaluation impacts growth. The fourth study looks at the contribution of the real exchange rate undervaluation, the tourism sector, and human capital development to the economic growth by using a panel data of selected microstates – many of which are small island nations-. In all four studies, the results are mainly in line with the theoretical expectations and/or with main previous empirical works. Our results provide evidence that real exchange rate undervaluation mainly has a positive impact on growth. Keywords: Economic growth, Exchange rate, Balassa-Samuelson effect, asymmetric relation, Tourism, human capital.

ÖZ: Ekonomistler, yıllar geçtikçe kötü yönetilen bir döviz kurunun, herhangi bir ekonominin büyüme çabalarına iyi geleceğinden çok zarar vereceği konusunda hemfikirdirler. Bununla birlikte, döviz kurları ve ekonomik büyüme arasındaki kesin ilişki iyi anlaşılmamıştır. Bu çalışmada, döviz kuru değer düşüklüğünün ekonomik büyüme üzerindeki etkisinin kapsamlı bir analizini yapmak için “reel döviz kuru ve ekonomik büyüme” konulu Rodrik (2008) raporu kullanılmıştır. Bu amaçla, bu tez dört bağımsız kısım olarak düzenlenmiştir. İlk iki kısımda, ekonomik büyümenin reel kurdaki değer düşüklüğünde gerilediği panel veri çalışmalarıdır. İki çalışma, birbirinden esas olarak iki şekilde farklılık gösterir. Birinci fark, para biriminin değer düşüklüğünün ölçülme şeklidir ve ikinci fark, büyüme denkleminin modellenme şeklidir. Kısacası, temel denge döviz kuru modeli olarak adlandırılan ikinci çalışma da Balassa-Samuelson etki temelli Rodrik yaklaşımı olarak adlandırılan ilk çalışmanın geliştirilmesi amaçlanmıştır. Üçüncü kısımda, reel döviz kuru değer düşüklüğünün zaman serileri analizini kullanarak ekonomik büyümeyi nasıl etkilediğini Almanya, Güney Afrika, Meksika ve Kamerun olmak üzere dört ülke için incelemektedir. Çalışmamız da ilişkilerin simetrik mi yoksa asimetrik mi olduğunu kontrol etmek için ve buna bağlı olarak, reel döviz kuru değer düşüklüğünün büyümeyi nasıl etkilediğini araştırmak için ARDL veya NARDL metodolojileri kullanılmıştır. Dördüncü kısımda, çoğu küçük ada ülkesi olarak seçilmiş mikro bölgelerin panel verilerini kullanarak reel döviz kuru değer düşüklüğünün, turizm sektörünün ve insan sermayesi gelişiminin ekonomik büyümeye katkısını incelemektedir. Dört çalışmanın hepsinde de sonuçlar temel olarak teorik beklentiler ve / veya önceki ana ampirik çalışmalar ile paraleldir. Sonuçlarımız, reel döviz kuru değer düşüklüğünün çoğunlukla büyüme üzerinde olumlu bir etkisi olduğuna dair kanıtlar sunmaktadır. Anahtar Kelimeler: Ekonomik büyüme, Döviz kuru, Balassa-Samuelson etkisi, asimetrik ilişki, Turizm, beşerî sermaye.
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Supervisor: Assoc. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; Exchane Rates--Effect of--Economic Growth; Economic growth; Exchange rate; Balassa-Samuelson effect; asymmetric relation; Tourism; human capital